Facilitators and barriers to community engagement in the Global Polio Eradication Initiative-A mixed methods study. - Priyanka Agrawal; Abigail Neel; Assefa Seme Deresse; Sue Gerber; Olakunle Alonge (Public Library of Science (PLoS), 2023)
Community engagement (CE) is an important component of public health research and program implementation, especially in low- and middle-income countries. More recently, CE activities have been utilized to develop partnerships in research and program implementation processes, and advocate for policy recommendations with the aim to improve acceptance and reduce disparities of public health research activities and benefits in the involved communities. Utilizing the tacit knowledge gained from the Global Polio Eradication Initiative, this paper highlights the contributors and challenges to the implementation of the GPEI program's community engagement initiatives from an implementers' perspective. The study took a mixed methods approach to analyze data collected from the Synthesis and Translation of Research and Innovations from Polio Eradication (STRIPE) project, which conducted an online survey and hosted key informant interviews with individuals who had been engaged with the GPEI program from 1988 onwards for at least 12 or more continuous months. An analysis of data limited to individuals (32%, N = 3659) who were primarily involved in CE activities revealed that around 24% were front-line healthcare workers, 21% were supervisors and 8% were surveillance officers. CE activities mainly focused on building trust within the communities, addressing misinformation, myths and fears around vaccinations, mobilization to reach high-risk or hard to reach populations, as well as building ownership and buy in from the communities. The strength of the implemental process of a program (38.7%) was among the key drivers of success, coupled with personal beliefs and characteristics of the implementers (25.3%). Social, political, and financial forces received mixed opinions as to their importance, depending on the stage of execution and readiness of the communities to accept the programs. Lessons learnt from the GPEI program provide tried and tested best practices and evidence for strategies that would work in diverse backgrounds with some customization to suit the needs of the situation.